Melting Curves of Triolein Polymorphs - Porde, Annette; Roßbach, Andre; Ferstl, Peter; Gillig, Sebastian; Werr, Ferdinand; de Ligny, Dominique; Wierschem, Andreas (Journal of the American Oil Chemists Society, 2021)
High-pressure treatment is a promising option for improving mechanical properties and processing parameters of fat-containing products. To identify optimum processing windows, melting curves, crystallization kinetics, and pathways for transferring the optimized structures to atmospheric pressure need to be known. Here, we provide melting curves of different polymorphic forms of triolein in the industrially relevant pressure range. The melting points of different polymorphic forms are detected optically in thin samples during stepwise changes of pressure or temperature. For cross-nucleated spherulites, this method allows determining the respective melting points of nuclei and overgrown structures. Tracing the melting curves to atmospheric pressure confirms previous identification of the polymorphic forms at high pressure and enables identifying a previously reported but undefined structure as the β2-form. Employing Raman spectroscopy, it is confirmed that the polymorph remained unaltered during the pressure release. With increasing pressure, the melting curves of the different polymorphic forms approach each other until they successively merge at the highest pressure levels studied.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Melting curves; Polymorphism; Pressure-induced crystallization; Raman spectroscopy; Triolein